Automatized protocol and interface to simulate QM/MM time‐resolved transient absorption at TD‐DFT level with COBRAMM. Issue 24 (11th July 2022) - Avagliano, Davide; Bonfanti, Matteo; Nenov, Artur; Garavelli, Marco
Abstract: We present a series of new implementations that we recently introduced in COBRAMM, the open‐source academic software developed in our group. The goal of these implementations is to offer an automatized workflow and interface to simulate time‐resolved transient absorption (TA) spectra of medium‐to‐big chromophore embedded in a complex environment. Therefore, the excited states absorption and the stimulated emission are simulated along nonadiabatic dynamics performed with trajectory surface hopping. The possibility of treating systems from medium to big size is given by the use of time‐dependent density functional theory (TD‐DFT) and the presence of the environment is taken into account employing a hybrid quantum mechanics/molecular mechanics (QM/MM) scheme. The full implementation includes a series of auxiliary scripts to properly setup the QM/MM system, the calculation of the wavefunction overlap along the dynamics for the propagation, the evaluation of the transition dipole moment at linear response TD‐DFT level, and scripts to setup, run and analyze the TA from an ensemble of trajectories. Altogether, we believe that our implementation will open the door to the easily simulate the time‐resolved TA of systems so far computationally inaccessible. Abstract : Schematic overview of the protocol implemented in COBRAMM to simulate transient absorption